EXPLORING ETHICAL CLEARANCE IN RESEARCH: STUDENTS' PERCEPTIONS - Citra Kurniawan; Herlin Pujiarti; Ence Surahman; Ubed Sonai Fahruddin Arrozi; Febri Taufiqurrahman; Nur Anita Yunikawati (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The need for research that meets the code of ethics increases along with the awareness of researchers to conduct research in accordance with ethical standards. However, awareness of the code of ethics is certainly not possessed by all academics, especially students. This study aims to explore students' perceptions of the code of ethics in conducting research and how perceptions influence students' views on the ethicals. The research method used in this study uses an experimental approach. This study involved 94 research participants in the study. Data analysis used in this study is validity, reality and correlation analysis. This study found that demographic data such as Gender, Semester Level and Research Subjects did not correlate with other variables. While the variable of importance of ethical clearance has a correlation with the impact of ethical violations, protection of research subjects and the responsibility of researchers and institutions.